Puritan responses to antinomianism in the context of reformed covenant theology: 1630-1696 - Caughey, Christopher Earl (Trinity College (Dublin, Ireland). School of English, 2013)
This thesis analyzes the way in which six seventeenth-century puritans from both sides of the Atlantic responded to antinomians—those accused of rejecting divine law—and the methods these six puritans used in their responses. In his book Blown by the Spirit (2004), David Como has divided seventeenth-century antinomians into two camps: “inherentists/perfectionists” and “imputationists.” The former were mystical and held esoteric beliefs, while the latter were more theological—even citing Martin Luther in their support. While this thesis does not focus on either group of antinomians, the six puritans whose microhistories are studied tended to focus their response on the imputationists. T.D. Bozeman has argued in The Precisianist Strain (2004) that a strict moralism and rigorous pietism permeated the puritan community and provoked the imputationists to an “antinomian backlash.” This thesis will employ the microhistories of John Cotton, Edward Fisher, John Owen, John Bunyan, Samuel Petto and Herman Witsius in an analysis of the controversy surrounding the antinomian backlash. Part of what makes these six figures so helpful in this analysis is their liminal status within the puritan community. Cotton, Owen and Petto were Independents and Bunyan was a Baptist—all outside the communions which tended to be in powerful positions like the Presbyterians and the Anglicans. Fisher probably held membership, but not office, in a Presbyterian church. Finally, Witsius was a minister in the Dutch Reformed Church and became an outside voice in the controversy only because a group of English puritans asked him to mediate their own conflict over antinomianism. Though the majority report among puritan theologians was that the Mosaic covenant which God made with Israel was simply one of many administrations of the one covenant of grace, this thesis has found that all six of the figures above believed that the Mosaic covenant was, in some sense, a covenant of works. The distinction between the covenant of works and the covenant of grace was the way the Calvinist wing of the Reformation developed Luther’s breakthrough regarding the sharp contrast between the law and the gospel. The law and the covenant of works were based upon the principle of justice so that curses were meted out for disobedience and rewards were bestowed for obedience. The gospel and the covenant of grace were based upon the principle of grace which meant that God freely gave believers salvific blessings on the basis of Jesus’ perfectly obedient life, sacrificial death and victorious resurrection. The significance of these six figures’ view of the Mosaic covenant as a covenant of works is that it provided them with a method to protect believers from the legalism, moralism and pietism that had provoked the antinomian backlash. Since the Ten Commandments had been imbedded in a covenant of works, those commandments could no longer threaten curses or promise rewards to believers who were no longer under the Mosaic covenant. Yet these six puritans also held that the substance of the Ten Commandments continued to bind all people—especially Christians—because the were the reflection of the character of the unchanging God and because they were written on the hearts of human creatures created in God’s image. Thus, Cotton, Fisher, Owen, Bunyan, Petto and Witsius all had what they perceived to be correction to offer the imputationist antinomians. This thesis analyzes the way in which six seventeenth-century puritans from both sides of the Atlantic responded to antinomians—those accused of rejecting divine law—and the methods these six puritans used in their responses. In his book Blown by the Spirit (2004), David Como has divided seventeenth-century antinomians into two camps: “inherentists/perfectionists” and “imputationists.” The former were mystical and held esoteric beliefs, while the latter were more theological—even citing Martin Luther in their support. While this thesis does not focus on either group of antinomians, the six puritans whose microhistories are studied tended to focus their response on the imputationists. T.D. Bozeman has argued in The Precisianist Strain (2004) that a strict moralism and rigorous pietism permeated the puritan community and provoked the imputationists to an “antinomian backlash.” This thesis will employ the microhistories of John Cotton, Edward Fisher, John Owen, John Bunyan, Samuel Petto and Herman Witsius in an analysis of the controversy surrounding the antinomian backlash. Part of what makes these six figures so helpful in this analysis is their liminal status within the puritan community. Cotton, Owen and Petto were Independents and Bunyan was a Baptist—all outside the communions which tended to be in powerful positions like the Presbyterians and the Anglicans. Fisher probably held membership, but not office, in a Presbyterian church. Finally, Witsius was a minister in the Dutch Reformed Church and became an outside voice in the controversy only because a group of English puritans asked him to mediate their own conflict over antinomianism. Though the majority report among puritan theologians was that the Mosaic covenant which God made with Israel was simply one of many administrations of the one covenant of grace, this thesis has found that all six of the figures above believed that the Mosaic covenant was, in some sense, a covenant of works. The distinction between the covenant of works and the covenant of grace was the way the Calvinist wing of the Reformation developed Luther’s breakthrough regarding the sharp contrast between the law and the gospel. The law and the covenant of works were based upon the principle of justice so that curses were meted out for disobedience and rewards were bestowed for obedience. The gospel and the covenant of grace were based upon the principle of grace which meant that God freely gave believers salvific blessings on the basis of Jesus’ perfectly obedient life, sacrificial death and victorious resurrection. The significance of these six figures’ view of the Mosaic covenant as a covenant of works is that it provided them with a method to protect believers from the legalism, moralism and pietism that had provoked the antinomian backlash. Since the Ten Commandments had been imbedded in a covenant of works, those commandments could no longer threaten curses or promise rewards to believers who were no longer under the Mosaic covenant. Yet these six puritans also held that the substance of the Ten Commandments continued to bind all people—especially Christians—because the were the reflection of the character of the unchanging God and because they were written on the hearts of human creatures created in God’s image. Thus, Cotton, Fisher, Owen, Bunyan, Petto and Witsius all had what they perceived to be correction to offer the imputationist antinomians.
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin